2011
DOI: 10.1111/j.1559-1816.2011.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Fools Fall in Love (at Work)? Factors Associated With the Incidence of Workplace Romance1

Abstract: We conducted 2 Web‐based survey studies to examine factors associated with the incidence of workplace romance. In Study 1, results based on data collected from 197 employees indicate that their degrees of perceived workplace sexualization and task interdependence were related to their observations of workplace romance. In addition, employees were most likely to report participating in a workplace romance when workplace sexualization and male–female social contact were high. In Study 2, results based on data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…Respondents indicated whether they were currently romantically involved with (e.g., dating, married to) someone who is employed by the same organization (1 ¼ No, 2 ¼ Yes, my spouse and I work for the same organization, 3 ¼ Yes, my domestic partner (i.e. someone you live with but are not married to) and I work for the same organization, or 4 ¼ Yes, I am dating someone who is employed by the same organization as I am) (see Pierce, 1998;Pierce and Aguinis, 2003;Salvaggio et al, 2011).…”
Section: Measures Of Control Variablesmentioning
confidence: 99%
“…Respondents indicated whether they were currently romantically involved with (e.g., dating, married to) someone who is employed by the same organization (1 ¼ No, 2 ¼ Yes, my spouse and I work for the same organization, 3 ¼ Yes, my domestic partner (i.e. someone you live with but are not married to) and I work for the same organization, or 4 ¼ Yes, I am dating someone who is employed by the same organization as I am) (see Pierce, 1998;Pierce and Aguinis, 2003;Salvaggio et al, 2011).…”
Section: Measures Of Control Variablesmentioning
confidence: 99%
“…Recent surveys, too, have used convenience samples: for example, Salvaggio et al . 's () survey of 197 working adults who had been recruited by undergraduate psychology students as part of an assignment, and their 2010 survey of 113 working adults from local businesses recruited by two graduate students. The strength of the surveys is that they have clearly demonstrated the prevalence of romance.…”
Section: Research Methods Used In Workplace Romance Researchmentioning
confidence: 99%
“…Attraction at work usually happens between those who work together closely, collaborate, are similar in attitude to each other and find it easy to interact (Byrne and Neuman ; Quinn ; Salvaggio et al . ). The increase in interaction as well as a sense of common purpose increases the likelihood of personal attraction.…”
Section: ‘Managing’ Power and Romancementioning
confidence: 97%
See 1 more Smart Citation
“…Gutek, Cohen, and Konrad (1990) found that non-work-related sexualized behavior such as sexual jokes, comments, and innuendo had no significant effect on employees' self-reports of romances at work, but did influence their tendency to others' romances. In a study based on data collected from 197 employees, Salvaggio, Streich, Hopper, and Pierce (2011) also found the tendency to observe others having a romance was related to perceived workplace sexualization, but also to task interdependence. Employees in this study, however, were most likely to report initiating a workplace romance when workplace sexualization and male-female social contact were high, although there was no relationship between task interdependence and the tendency to initiate a workplace romance.…”
Section: The Context Of Workplace Romancesmentioning
confidence: 99%